GSK3 inhibition reduces inflammatory responses of microglia and upregulates Il-10 production - Md Zain, Zuhaida; Vidyadaran, Sharmili; Hassan, Masriana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Neurodegeneration resulting from pathogen invasion or tissue damage has been associated with activation of microglia, and exacerbated by the release of neurotoxic mediators such as pro-inflammatory cytokines, chemokines and reactive oxygen species. Activation of microglia stimulated by lipopolysaccharide is mediated in part by GSK-3 signaling molecule. Induced IL-10 expression via GSK-3 inhibition is noteworthy since IL-10 has been remarkably shown to suppress inflammation. Objectives: We aimed to inactivate microglia through inhibition of GSK-3 signaling and to determine its effects on the production of pro- and anti-inflammatory mediators. Methods: LPS-stimulated BV-2 cells were treated with a GSK-3 inhibitor (LiCl, NP12, SB216763 or CHIR99021). Inhibition of GSK-3 was determined by the phosphorylation status of GSK-3β. The effects of GSK-3 inhibition on microglial inflammatory response were investigated by examining various mediators and CD200R marker. Production of nitric oxide (NO), glutamate and pro- and anti-inflammatory cytokines were measured using flow cytometry, Griess assay, glutamate assay and Cytometric Bead Array (CBA) respectively. Results: GSK-3β signaling in LPS-stimulated microglia was blocked by GSK-3 inhibitor through increased phosphorylation at Serine 9 residue. GSK-3 inhibitors had also led to reducing in microglia activity via increased expression of CD200R. Inhibition of GSK-3 also diminished inflammatory mediators such as nitric oxide (NO), glutamate, pro-inflammatory cytokines (TNF-α and IL-6) and chemokine, MCP-1. Reduction of pro-inflammatory mediators by GSK-3 inhibitor was coincided with increased IL-10 production. Conclusions: Suppression of microglia-mediated inflammatory response was facilitated by GSK-3 inhibition with associated increased in IL-10 production.